A Crowded and Growing Shelf - Britton, Gregory (International Higher Education, 2025)
<h3 id="books-once-defined-scholarly-communication-however-declining-institutional-support-and-library-purchasing-are-reshaping-scholarly-communications-academic-publishing-and-the-nature-of-academic-work-itself-what-emerges-is-a-different-publishing-landscape-and-experimental-forms-like-open-access-and-open-peer-review-at-the-same-time-many-scholars-are-shifting-their-communications-to-faster-moving-and-more-democratic-digital-forms" data-pm-slice="1 1 []">Books once defined scholarly communication. However, declining institutional support and library purchasing are reshaping scholarly communications, academic publishing, and the nature of academic work itself. What emerges is a different publishing landscape and experimental forms like open access and open peer review. At the same time, many scholars are shifting their communications to faster moving and more democratic digital forms.